2021
DOI: 10.3390/vaccines9070701
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Determinants of COVID-19 Vaccine Acceptance among Healthcare Workers in Kuwait: A Cross-Sectional Study Using the 5C and Vaccine Conspiracy Beliefs Scales

Abstract: Acceptance of coronavirus disease 2019 (COVID-19) vaccination appears as a decisive factor necessary to control the ongoing pandemic. Healthcare workers (HCWs) are among the highest risk groups for infection. The current study aimed to evaluate COVID-19 vaccine acceptance among HCWs in Kuwait, with identification of the psychological determinants of COVID-19 vaccine hesitancy. The study was conducted using an online anonymous survey distributed between 18 March 2021 and 29 March 2021. The sampling strategy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
139
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 76 publications
(116 reference statements)
21
139
1
2
Order By: Relevance
“…Furthermore, collective responsibility, defined as the willingness to protect others by the means of one's own vaccination, was observed to be an important factor in COVID-19 vaccination intention in this study. While this result is also found in other populations, such as health professionals [20,28] and older populations [29,30], it may have been underestimated in younger individuals. In our study, students who rated high on collective responsibility showed five-times higher odds of getting vaccinated than students who rated lower.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, collective responsibility, defined as the willingness to protect others by the means of one's own vaccination, was observed to be an important factor in COVID-19 vaccination intention in this study. While this result is also found in other populations, such as health professionals [20,28] and older populations [29,30], it may have been underestimated in younger individuals. In our study, students who rated high on collective responsibility showed five-times higher odds of getting vaccinated than students who rated lower.…”
Section: Discussionmentioning
confidence: 50%
“…49 Use of social media was significantly associated with lower acceptance rates in Kuwait. 76 Physicians or other health colleagues were cited as the main source of information for health workers in Egypt (30%), 74,71 and were also considered important in Jordan 49 and Kuwait. 76 Around 54% of health workers in an Egyptian study were advised by their hospital or health centre to accept the vaccine, and those participants had 2.5 higher odds of accepting the vaccine than their counterparts who had not received such advice.…”
Section: The Communication Environmentmentioning
confidence: 99%
“…76 Physicians or other health colleagues were cited as the main source of information for health workers in Egypt (30%), 74,71 and were also considered important in Jordan 49 and Kuwait. 76 Around 54% of health workers in an Egyptian study were advised by their hospital or health centre to accept the vaccine, and those participants had 2.5 higher odds of accepting the vaccine than their counterparts who had not received such advice. 71 In Lebanon, health authorities' or health facilities' recommendation to vaccinate by was positively linked to vaccine acceptance and stood out as one of the most important cues for vaccination.…”
Section: The Communication Environmentmentioning
confidence: 99%
See 2 more Smart Citations